Information technology and computational physics - Kulczycki, Piotr; Kóczy, László T.; Mesiar, Radko; Kacprzyk, Janusz (Springer, 2017)
A broad spectrum of modern Information Technology (IT) tools, techniques, main developments and still open challenges is presented. Emphasis is on new research directions in various fields of science and technology that are related to data analysis, data mining, knowledge discovery, information retrieval, clustering and classification, decision making and decision support, control, computational mathematics and physics, to name a few. Applications in many relevant fields are presented, notably in telecommunication, social networks, recommender systems, fault detection, robotics, image analysis and recognition, electronics, etc. The methods used by the authors range from high level formal mathematical tools and techniques, through algorithmic and computational tools, to modern metaheuristics.
Keywords: Information technology.; Physics -- Data processing.; elektronické knihy; electronic books